Analisis Sensori Terhadap Sirup Buah Pedada (Sonneratia Caseolaris) Di Kabupaten Ketapang - Selvianti, Isye (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2022)
This study seeks to identify the non-blended boiling process and the blended heating process in the manufacturing of mangrove apple syrup, as well as to identify the rate at which the mangrove apple syrup product is accepted by consumers. Non blended method on mangrove apple (Sonneratia caseolaris) syrup production process is a method in which the mangrove apple that have been cleaned and chopped into parts, with the addition of 65% of sugars and 100ml of water, therefore the boiling process started for 30 minutes with the temperature of ±100°C. While the blended method done by blending the cleaned mangrove apple with 1000ml of water and then filtered in order to obtain the exact, after that add 65% of sugars, therefore begin the heating process for 30 minutes with the temperature of ±100°C until it thickened. Analysis that will be ran is a sensory test by 30 partially trained panelists. Analysis result of mangrove apple syrup sensory test for the color, flavor, and smell, the best version of mangrove apple jam is the one with the blended method, with the testing score of brownish red colored,a hedonic test of iconic smell of mangrove apple that is tolerable, and a pleasant taste.